A new species of the genus Nothrholaspis Berlese (Acari: Macrochelidae) from Iran - Babaeian, Esmaeil; Joharchi, Omid; Jamshidian, Maryam Keshavarz (Zootaxa, 2014)
A new mite species of the genus Nothrholaspis Berlese, Nothrholaspis saboorii Babaeian & Joharchi sp. nov., is described and illustrated from specimens collected from soil in the Karaj region of Iran. An identification key for the known species of Nothrholaspis is presented.